NURSING ASSISTANCE TO WOUNDS BEARERS: TECHNOLOGIES OF CARE DEVELOPED IN THE PRIMARY ATTENTION - Josefine Busanello; Fernanda Machado da Silva; Graciela Dutra Sehnem; Marcia Adriana Poll; Luise Monteiro Lobão de Deus; Thyelle da Silva Bohlke (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928532 Aim: to know the care technologies implemented in the care of individuals with wounds in primary care units of a city in the interior of Rio Grande do Sul. Method: the study subjects were eight nurses working in these health units. Data collection was conducted in July 2012, using the focus group technique. Results: from the analysis were structured three thematic categories: Communication and relationship mediation care to individuals with wounds; systematization of nursing care to individuals with wounds, and topical therapies in the care of individuals with wounds. Final considerations: the scope of nursing care to individuals with wounds is essential to the implementation of soft technologies, soft-hard and hard. However, the need to dominate light technologies, considering the perspective represented by primary care.